Planful Self-Control, Metabolic Risk, and Psychosocial Outcomes Among Young, Black Men: A Test of Skin-Deep Resilience Theory - Kogan, Steven M.; Reck, Ava J.; Curtis, Michael G.; Zuercher, Heather; Collins, Christopher; Kwon, Elizabeth; Augustine, Danielle A. (Frontiers in Psychology, 2022)
Research on skin-deep resilience suggests that for youth and young adults from disadvantaged backgrounds, high levels of planful self-control may promote positive psychosocial outcomes while simultaneously conferring vulnerabilities to chronic diseases related to aging. In this study, we investigated the divergent effects of planful self-control on young Black American men’s psychosocial well-being and their metabolic risk. We expected that high levels of planful self-control in emerging adulthood would predict positive outcomes in young adulthood (educational attainment, low depressive symptoms, job satisfaction); however, the combination of high levels of planful self-control and the experience of contextual adversity either in emerging adulthood or in childhood would forecast poor metabolic health. Hypotheses were tested with prospective data from 504 Black American men followed from age 20 to age 26. Planful self-control in emerging adulthood directly forecasted low levels of depressive symptoms, one’s likelihood of obtaining a bachelor’s degree, increased job satisfaction, and increases in metabolic risk. Exposure to childhood deprivation moderated the influence of planful self-control on metabolic risk. Men with high levels of deprivation and high levels of planful self-control exhibited the worst metabolic profiles in the sample. In contrast, men with high levels of childhood deprivation and low levels of planful self-control exhibited the best metabolic profiles. Documenting the health consequences associated with planful self-control provides a foundation from which to identify modifiable psychosocial factors that affect the course of psychosocial problems and health.